Hypertension Management in Primary Health Care Centres: Blood Pressure Control and Classes of Antihypertensive Medication, Khartoum State, 2018 - Maha A. G. Magboul,; Egbal A. B. A. Karaig,; Ibtisam A. Ali, (Public Health, 2021)
BackgroundIn Sudan, the delivery of care based on the primary health care (PHC) level, which is the first contact with the health system. PHC is the level at which the modifiable risk factors for hypertension are addressed together with the treatment of known hypertensive patients. ObjectiveTo assess the management of hypertension in PHC in Khartoum State, 2018. Material and MethodsThe study was a descriptive cross-section, health centre’s based that covered six PHC centres in Khartoum State. The study in-terviewed all diagnosed Sudanese hypertensive patients more than 18-years of age who attended the selected PHC centres. The research team collected data using a structured questionnaire and measuring the blood pressure (BP) with a mercury sphygmo-manometer. The study variables were demographic characteristics and disease features as independent variables and hypertension control as the dependent variable. The statistician analyzed the data using the statistical package for the Social Science version 21.0 and the Chi-square (χ) test to obtain the p value to test the association between the addressed variables. The study group adopt ethical considerations throughout the study. ResultsOf the 384 hypertensive patients interviewed in this study, 57% were females and 47.7% were more than 60-years of age. A large percent of the subjects were either primary educated or illiterate (32.6%, 19.8% respectively). More than half of the hyperten-sive patients (52.1%) were uncontrolled and 52.9% had no comorbidities. Diabetes was predominant (39.3%) among those who had comorbidities. The majority of the patients (92.7%) were adherent to the medication. Of the studied patients, 58.1% used monotherapy. The most controlled patients were the elderly and middle-aged patients and the highly educated patients (p=0.005). Patients with a duration less than five-years were more likely to be controlled (p=0.036). The majority of the patients who used combined treatment were found to be controlled. ConclusionThis study concluded that the high prevalence of uncontrolled hypertensive patients attending PHC was mainly attributed to the use of monotherapy, presence of comorbidities and medication non-adherence. The latter is related to patients’ ignorance, financial constraints and dislike of using many drugs during the day. In addition, the use of combined therapy, elder age and high education were factors for better control.